THE IMPACT OF GLOBALIZATION: TRANSFORMATION OF LANGUAGE AND CULTURAL IDENTITY IN THE SPECIAL REGION OF YOGYAKARTA - Odang Hermanto; Nisa Nurhasanah; Dina Aprilia; Tia Apianti; Ujang Muhamad Ramdan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Yogyakarta is a city historically rich in Javanese traditions and values. With increasing global interaction through information technology, tourism, and cultural exchange, Yogyakarta's socio-cultural landscape is undergoing significant changes. This study analyzes how the Javanese language, as the core of local cultural identity, faces challenges and adapts amidst the dominance of English and standard Indonesian. Shifts in language use, particularly among the younger generation, not only affect the preservation of Javanese dialects and speech levels but also reshape their perceptions of tradition and modernity. Furthermore, this abstract highlights how globalization influences cultural identity through cultural hybridization, where foreign cultural elements assimilate with local practices, creating new forms of expression that sometimes blur the boundaries of indigenous identities. While globalization brings positive impacts such as increased access to information and economic opportunities, there are also concerns about the erosion of traditional values ​​and cultural homogenization. This study concludes that Yogyakarta stands at a crossroads between preserving its cultural heritage and embracing global change, highlighting the importance of adaptive cultural conservation strategies and strong language education to maintain its unique identity.